Basic identities for additive continuously distributed sequences - Gusak, D. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
For an additive sequence ξ(n), we establish basic factorization identities and express the distributions of limiting Junctionals (extremum values of ξ(n), the time and value of the first jump over a fixed level, etc.) in terms of the components of factorization.